A review on somaclonal variation of Theobroma cacao L. / Ahmad Muzzammil Bakri - Bakri, Ahmad Muzzammil (Faculty of Plantation and Agrotechnology, 2019)
Theobroma cacao L. (Cocoa) is mainly grown in the tropical regions of the world, at rain forest areas and domestically cultivated for its beans production. Tissue culture is one of the important tools for plant breeding and research. The presence of somaclonal variation derived from tissue culture could cause changes in the plant. The change in agronomic traits is the sources to new clones/variants either the traits is positive or negative. In developing somaclonal variation of Theobroma cacao L. each of the tissue culture method has different result. Besides, the problem of somaclonal variation is not only caused by one factor and somaclonal variation is random and unpredictable phenomena. Besides, there is a problem in determining the best method in detecting somaclonal variations in cocoa. This review provides an overview of the possible factors of somaclonal variation that may cause by pre-existing variation or tissue culture induced variation. Pre-existing variation factor listed are chimeras, chromosomes aberration and rearrangement, cell cycle and transposable element. Induced variation reviewed are propagation method, explants source, type and concentration of plant growth regulator (PGR), number and duration of subculture, effect of stress and genotype and ploidy level. This review focused on the effects of somaclonal variation either positive, negative or positive-negative effect and techniques to overcome somaclonal variation using morphological, physiological/biochemical and molecular detection.